Social Network Analysis: Applied Tool to Enhance Effective Collaboration between Child Protection Organisations by Revealing and Strengthening Work Relationships - Dávid, Bea (European Journal of Mental Health, 2013)
Applied Tool to Enhance Effective Collaboration between Child Protection Organisations by Revealing and Strengthening Work Relationships: In 2009, an organizational research was led by the Social Work department of the Veszprém College of Theology on how the child protection system of children actually operates. Mixed methodology was used. In-depth interviews were conducted (N = 58) among the different actors of the child protection system. The qualitative approach was complemented by social network analysis. Revealing the mechanism based on the actors’ perception on how the child protection network operates, we identified and named the strengths and weaknesses of its structure. We also enumerated the interviewees’ propositions that can be the pillars of a future co-operation. Our conclusion is a little bit atypical in the sense that in our study we could report positive changes implemented since 2009. The aim of our study is to show how social network analysis can be a useful tool to help professionals’ collaboration in the social field.